Pelatihan Penyusunan Instrumen Tes Matematika Online Berbasis PISA Bagi Guru matematika SMP Bengkulu - Edi Susanto; Agus Susanta; Rusdi (JPM: Jurnal Pengabdian Masyarakat, 2022)
One of the reference standards in measuring the understanding of secondary school students at the international level is the Program for International Student Assessment (PISA) survey. This is also supported by the implementation of a minimum competency assessment (AKM) in 2021 with a focus on numeracy and literacy skills. However, the results of the PISA survey in 2018 Indonesia only ranked 72 out of 78 participating countries. One of the contributing factors is that students are not accustomed to solving PISA-based questions. So that training on the preparation of PISA-based online mathematics test instruments was carried out. This training activity aims to design a PISA-based online mathematics test instrument. The activity was held at the Bengkulu City Mathematics MGMP which was attended by 45 SMP/MTs mathematics teachers. The implementation of the preparation consists of four stages, namely: (1) module design, (2) question preparation training, (3) structured assignments, (4) online test design. The results of the activity were composed of 25 online PISA test instruments that met the valid criteria. The results of the teacher's response to the training activities on the criteria are good